HOW VISITATION AFFECTS THE BEHAVIOR AND WELFARE OF DIFFERENT SPECIES OF CAPTIVE AMAZONIAN PRIMATES? - Leal, Liliane Monteiro; Souza, Luciane Lopes; Santos, Lorena Sarmento dos (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2022)
This study had the purpose of understanding the effects of visitation on behavioral patterns and on the well-being of primates in captivity. Five Amazonian primate species were observed using the focal animal method: Ateles chamek, Ateles belzebuth, Ateles paniscus, Lagothrix cana, and Sapajus apella. Two categories of visitor behavioral observations were adopted - active and passive. From the total number of records, the behavior of primates could be observed in 53.7% of the notes in the presence of visitors. The behavior of the visitors in front of the cages was considered passive in 91.2% of those records. The three species of Ateles reacted in different ways in the presence and absence of visitors. The type of visitor behavior had influence on the behavior of the primate (Chi-square=22.9, p<0.001). Stress indicating behaviors (CIE) represented 3.3% of the behavioral repertoire of the species (n=253 records). The primates presented a varied number of CIE, which included indexes of reduced well-being levels. A. belzebuth was ranked first as the species most affected by visitation. These results show the importance of understanding the stress effects on the behavioral pattern of captive primates in relation to visitation and other factors, leading to alternative actions for the zoo in order to improve the level of their welfare.